IFPA meeting 2016 workshop report I: Genomic communication, bioinformatics, trophoblast biology and transport systems. (December 2017) - Albrecht, Christiane; Baker, Julie C.; Blundell, Cassidy; Chavez, Shawn L.; Carbone, Lucia; Chamley, Larry; Hannibal, Roberta L.; Illsley, Nick; Kurre, Peter; Laurent, Louise C.; McKenzie, Charles; Morales-Prieto, Diana; et al.
Abstract: Workshops are an important part of the IFPA annual meeting as they allow for discussion of specialized topics. At IFPA meeting 2016 there were twelve themed workshops, four of which are summarized in this report. These workshops covered innovative technologies applied to new and traditional areas of placental research: 1) genomic communication; 2) bioinformatics; 3) trophoblast biology and pathology; 4) placental transport systems.